Operation of dry distillation process on the production of radionuclide 131I at Puspiptek area Serpong Indonesia, 2021 to 2022 - Chaidir Pratama; Daya Agung Sarwono; Ahid Nurmanjaya; Abidin Abidin; Triyatna Fani; Moch Subechi; Endang Sarmini; Enny Lestari; Yanto Yanto; Kukuh Eka Prasetya; Maskur Maskur; Fernanto Rindiyantono; et al. (Nuclear Engineering and Technology, 2024)
131I is a fission product produced in a nuclear reactor by irradiating tellurium dioxide, with a half-life of 8.02 day. The most important and widely used method for making 131I is irradiation using a nuclear reactor and post-irradiation followed by dry distillation. The advantage of the dry distillation process is that the process and the equipment are relatively simple, namely TeO2 (m.p. 750 °C), which can withstand heating during reactor irradiation. Based on TeO2 irradiation by neutron following the technique of dry distillation was explained for production of 131I on a large scale. A dry distillation followed the radioisotope production operation using the 30 MW GA Siwabessy nuclear reactor to meet national demand. TeO2 targets are 25 and 50 g irradiated for 87–100 h. The resulting 131I activity is 20.29339–368.50335GBq. According to the requirements imposed on the radionuclide purity of the preparation, the contribution of 131I training in the resulting preparation was not less than 99.9 %